Hukum Dan Keadilan Serta Kelangsungan Hidup Manusia - Usman - (Jatiswara, 2012)
The title of article is The Law and Justice with the Life of Human in Islamic Perspective with the aim is to give the description about the rule of law in regualating the human life, so that created the properity,safety, peacefulness in social life. The analysis which is used in this article is descriptive analysis that conducted by library studi, it means that the author use the main data is secondary data that obtained from the relevant references,then it is analyzed an described. According to the result of analysis indicate that, the performance of human life is needed the existence of norms of law to regulate the human life in the social function in order to be created the safety and peacefulnees in society. For attaining that condition is needed the fairness,than the fairness can be obtained if there is equality,between rights and obligation on each person and the full responsibility.